'I accept it [staff assistance]; no choice': an ethnographic study of residents' attitudes towards mobility within nursing homes. (26th April 2013) - Taylor, Janice; Sims, Jane; Haines, Terry P.
<x xml:space="preserve">Abstract</x> Background Mobility contributes to the quality of life and independence of residents in nursing homes. To perform resident‐centred mobility care, staff need to understand residents' physical capacity and perspectives of care. Aims and objectives The aim of the study was to explore residents' perspectives of intrinsic factors influencing their mobility and associations between these factors with a view to informing resident mobility care practice improvements. Design The study was part of a larger ethnographic project exploring safe resident mobility care in nursing homes. Methods Semi‐structured interviews with nursing home residents supplemented by non‐participant observations were conducted over a 20‐month period from July 2010. Fifteen residents consented to be interviewed in three nursing homes in Melbourne, Australia. Unobtrusive observations of 46 mobility events took place in three nursing homes over 5 months from September, 2011. Results Participants identified intrinsic factors that influence their mobility including mobility capacity, strategies to cope with mobility loss, motivation and efforts to remain mobile. Three themes related to resident attitudes and responses to mobility loss emerged: acceptance of mobility loss and staff assistance; motivation to remain mobile; and acquiescence and loss of control during mobility events. A conceptual model developed from the study outlined associations between resident attitudes and mobility and quality of life outcomes. Discussion was framed by theories of ageing and adaptation: selection, optimisation and compensation; learned dependency; and learned helplessness. Conclusion Resident acceptance of mobility loss, and required staff assistance and realistic determination to remain mobile contribute to residents' quality of life. Mobility care based on considerations of resident choice, autonomy and the value of mobility is important. Implications for practice The model developed from this study can guide staff manual handling training and practice towards improved resident‐centred approaches to mobility care.